Sisterland [compact disc, unabridged] : a novel - Sittenfeld, Curtis (Random House Audio : Books on Tape, 2013)
From an early age, Kate and her identical twin sister, Violet, knew that they were unlike everyone else. Kate and Vi were born with peculiar 'senses,' innate psychic abilities concerning future events and other people's secrets. Though Vi embraced her visions, Kate did her best to hide them.